Teachers’ perception of emergency remote learning in Portugal during COVID-19 pandemic - Cruz, Sara Maria Alves (2022)
The COVID-19 pandemic has highly impacted our society, particularly educational professionals, on their daily routines and changing the way they work. COVID-19 spread quickly, and we had to take urgent action on closing schools so teachers would continue to teach their students and put stringent measures such as national lockdowns and social distancing initiatives. The present study aims to understand teachers' perceptions regarding the operationalization of Emergency Remote Learning in Portuguese schools. The study also seeks to measure differences in satisfaction level, attitudes, and challenges across teaching methodology adopted by teachers. It will be used as a quantitative study, using a survey as a technical procedure for data collection to meet the proposed objectives. Data collection lasted two months, implemented through the availability of the study online on social networks, for teachers to respond voluntarily. Findings show that the COVID-19 pandemic and social distancing requirement has presented undue challenges for all education stakeholders, especially teachers. The teachers felt exhausted, but they recognized that the Technology has made a significant contribution and showed a willingness to learn more to integrate technologies into their practice and recognize the importance of this being done effectively.